2020
DOI: 10.21107/jk.v13i3.7550
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Temporal Sebaran Suhu Permukaan Laut Tahun 2018 Hingga 2020 Dengan Data Citra Terra Modis

Abstract: Sea surface temperature (SPL) information is the most important water quality parameter in the ocean, especially in coastal areas. Remote sensing technology with Terra Modis satellite data is used for periodic monitoring of SPL changes. The purpose of this study was to analyze the temporal distribution of SPL on the coast of Malang, East Java. The data used are SPL data from Terra-MODIS satellite sensors in May 2018, 2019 and 2020. Analysis of the data used is descriptive analysis which includes temporal analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
(5 reference statements)
0
4
0
2
Order By: Relevance
“…The increase in temperature of the earth can be seen through the sea surface temperature in 2018 ranged between 25° C-26° C, in 2019 ranged between 26°C-27°C, the year 2020 ranging from 30°C-31°C. On May 23, 2020, it became the highest sea surface temperature value, reaching 30,8°C [3]. The results of the study in 2020 showed that the SPL reached a higher value than in 2019.…”
Section: Introductionmentioning
confidence: 87%
“…The increase in temperature of the earth can be seen through the sea surface temperature in 2018 ranged between 25° C-26° C, in 2019 ranged between 26°C-27°C, the year 2020 ranging from 30°C-31°C. On May 23, 2020, it became the highest sea surface temperature value, reaching 30,8°C [3]. The results of the study in 2020 showed that the SPL reached a higher value than in 2019.…”
Section: Introductionmentioning
confidence: 87%
“…Fluktuasi nilai suhu permukaan laut di perairan Teluk Weda selama penelitian cukup fluktuatif dengan kisaran suhu rata-rata 27.4 -30.0 o C, dimana kondisi suhu permukaan tersebut masih dalam kisaran suhuuyang baik bagi kehidupan organismeeperairan karena kondisi ini masih dalamMkisarannyang disukai oleh biota perairan, yakni 18-30 °C [16,17]. Suhu permukaan laut memegang peran penting bagi biota laut karena, parameter oseanografi ini mempengaruhi pergerakan massa air secara horizontal dan vertikal [18]. Menurut Yuniarti et alt [19] suhuuair berpengaruh terhadap sistem metabolism bioat air laut, regerasi bahkan terhadap habitat tempat bioata di perairan laut.…”
Section: Distribusiispasialldanntemporallsuhuupermukaannlauttunclassified
“…In April, May and June the average sea surface temperature ranges from 31.16-31.34 o C. In that month the waters of the Strait of Malacca experienced summer, resulting in sea surface temperatures that increased from an average of 30 o C to 31 o C. After June the average sea surface temperature returned to 30 o C and at optimum temperatures will have a good impact on small pelagic fish organisms in the waters of the Strait of Malacca. States that high sea surface temperatures in the water can disrupt the balance of ecosystems in sea waters because every marine organism is able to adjust to the temperature at a certain limit [7].…”
Section: Sea Surface Temperaturementioning
confidence: 99%
“…If primary productivity in the waters increases then the CPUE of the fish will decrease and if the primary conductivity decreases then the CPUE will increase even if it is not significant. There are aspects that affect sea surface temperatures, namely hydrological cycles, rainfall intensity and consequently have a less favorable impact on ecosystems in the environment [7]. The results of the analysis that has been carried out on the relationship between sea surface temperature with chlorophyll-a concentration value and primary productivity value based on pearson analysis should be on temperature and chlorophyll-a if the temperature rises at the optimum point (Close to the value of 30 o C) then the value of chlorophyll-a concentration will increase and followed by the productivity value primer increased as well, but found in the figure 7 that shows a mismatch, namely in 2017 and 2018, this is due to monsoon winds that bring seasonal changes that make certain months and years.…”
Section: Pearson Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation